Research Development of Radiation-Induced Lymphopenia - Yue WANG; Hui ZHU (Zhongliu Fangzhi Yanjiu)
When radiotherapy is administered, many patients exhibit a reduction in lymphocyte numbers due to the inherent radio-sensitivity of lymphocytes. In particular, they experience a decrease in CD8+ T cells, which may weaken their mediated antitumor immune response. While radiotherapy activates the immune system, it can also lead to a certain degree of immunosuppression. Current research suggests that the formation mechanism of radiation-induced lymphopenia (RIL) involves multiple factors, including increased radiation exposure to lymphocytes and the application of lymphocytotoxic drugs. The adverse impact of RIL on patients’ clinical outcomes can be mitigated, to some extent, by actively optimizing radiotherapy dosimetric parameters to maximally protect lymphocytes.